Elevated relative risk of aneurysmal subarachnoid hemorrhage with colder weather in the mid-Atlantic region. Issue 10 (October 2015) - Rivera-Lara, Lucia; Kowalski, Robert G.; Schneider, Eric B.; Tamargo, Rafael J.; Nyquist, Paul
Abstract We have previously reported an increase of 0.6% in the relative risk of aneurysmal subarachnoid hemorrhage (aSAH) in response to every 1°F decrease in the maximum daily temperature (Tmax) in colder seasons from patients presenting to our regional tertiary care center. We hypothesized that this relationship would also be observed in the warmer summer months with ambient temperatures greater than 70°F. From prospectively collected incidence data for aSAH patients, we investigated absolute Tmax, average daily temperatures, intraday temperature ranges, and the variation of daily Tmax relative to 70°F to assess associations with aSAH incidence for patients admitted to our institution between 1991 and 2009 during the hottest months and days on which Tmax > 70°F. For all days treated as a group, the mean Tmax (± standard deviation) was lower when aSAH occurred than when it did not (64.4 ± 18.2°F versus 65.8 ± 18.3°F; p = 0.016). During summer months, the odds ratio (OR) of aSAH incidence increased with lower mean Tmax (OR 1.019; 95% confidence interval 1.001–1.037; p = 0.043). The proportion of days with aSAH admissions was lower on hotter days than the proportion of days with no aSAH (96% versus 98%; p = 0.006). aSAH were more likely to occur during the summer and on days with a temperature fluctuation less than 10°F (8% versus 4%; p = 0.002). During the hottest months of the year in the mid-Atlantic region, colder maximum daily temperatures, a smaller heat burden above 70°F, and smaller intraday temperature fluctuations are associated with increased aSAH admissions in a similar manner to colder months. These findings support the hypothesis that aSAH incidence is more likely with drops in temperature, even in the warmer months.